2013
DOI: 10.1111/grs.12033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting height on the chemical composition, nutritional value and yield, fermentative quality and aerobic stability of corn silage and relationship with plant maturity at harvest

Abstract: The experiment was carried out to investigate the effects of cutting height at harvest on the nutritional and fermentative properties and yield per unit area of corn (Zea mays L.) silage in relation to the maturity of the corn plants at the time of harvest. Corn forage at the early or late dent stage was harvested at normal (30 cm) or high (78 cm) heights. After the yield of fresh matter and dry matter per ha was recorded, whole‐crop corn silage was prepared. After 60 days of the ensiling, the samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Milk fat yield, milk protein concentration, and milk protein yield were unaffected by the treatments. Results suggest that well-fermented snaplage may have a high starch digestibility, and diets may need a source of starch with lower Summary of 7 studies: Neylon and Kung (2003), Bernard et al (2004), Lewis et al (2004), Kung et al (2008), Aoki et al (2013), Nigon et al (2016), Ferraretto et al (2017). Not all studies reported all parameters.…”
Section: Snaplagementioning
confidence: 99%
“…Milk fat yield, milk protein concentration, and milk protein yield were unaffected by the treatments. Results suggest that well-fermented snaplage may have a high starch digestibility, and diets may need a source of starch with lower Summary of 7 studies: Neylon and Kung (2003), Bernard et al (2004), Lewis et al (2004), Kung et al (2008), Aoki et al (2013), Nigon et al (2016), Ferraretto et al (2017). Not all studies reported all parameters.…”
Section: Snaplagementioning
confidence: 99%
“…However, these early studies were conducted with steers of only one age group, and the canes were separated into only two vertical sections (tops and stalks). Considering that there may be a gradual change in forage quality, such as fibre and energy content, from top to bottom of the canes, it is likely that intake and animal performance follow the same pattern of change as found for other forage crops (Aoki et al 2013). Since older animals can apply a greater bite force than young animals (Benvenutti et al 2008), it is likely that the reduction of intake and animals' performance from top to bottom of the sugarcane may be more pronounced in younger animals due to the presence of tougher material at the bottom of the plant.…”
Section: Introductionmentioning
confidence: 95%
“…The increase in DM and digestible DM yields associated with the increasing plant maturity is consistent with previous research won silage crops (Marsalis et al ., 2010; Atis et al ., 2012; Aoki et al ., 2013). For example, Monks et al .…”
Section: Discussionmentioning
confidence: 99%